P642 Neonatal gastric duplication cyst: a case report. (June 2019) - Hamed, Amel Ben; Charfi, Manel; Zitouni, Hayet; Regaieg, Chiraz; Bouraoui, Amira; Regaieg, Ridha; Hmida, Nedia; Mhiri, Riadh; Thabet, Afef Ben; Gargouri, Abdellatif
Abstract : Background: Gastrointestinal duplication(GID) cysts are rare congenital malformations. It occurs approximately in 1 out of 10.000 births. It can occur at any part of the alimentary tract. Gastric duplication cyt constitute 2 to 7% of all GID. They are usually cystic and located on the greater curvature, and ; have no communication with the gastric lumen. GID are diagnosed most commonly in the first 2 years of age. Early diagnosis and surgical correction in the neonatal period usually are advocated to ovoid potential morbidity and mortality. Case report: In this report, we present a 3-days-old newborn with antenatal diagnosis of gastric duplication confirmed postnatally. It was successfully managed using open surgical resection. Histology confirmed the diagnosis. The postoperative course was unevent full. At 5 months, the infant had a good follow-up. Conclusion: Gastric duplications are very rare in newborns. Symptoms are atypical. Antenatal diagnosis is possible and allowed planning management. The treatment is based on a complete excision. Laparoscopic surgery is successful but needs to prove its safety and effectiveness.